Address by Francesco Bandarin, UNESCO Assistant Director-General for Culture on the occasion of the inauguration of the exhibition: Erró, Saga of American Comics 1973-1999;UNESCO, 29 April 2014 - Bandarin, Francesco (29 Apr. 2014, 2014)
Electronic version only